The new strategic directions of rural development in Hungary - Szabóné Pap, Hajnalka; Bezzeg, Enikő (Applied Studies in Agribusiness and Commerce, 2012)
The notion of sustainability is the basis for our future possibilities. Local sustainability, in the centre of which can be found the livable settlement, is especially important in rural areas.Without developing rural areas, there is no developing society. The growth of the Earth’s population and the world economy has already surpassed the carrying capacity of this planet which may result in an “overshoot and collapse”. This can still be prevented today. The population of towns and cities is rapidly increasing. Urbanization is a very fast process, even in Hungary. In large cities with millions of inhabitants crime and lumpen lifestyle pose huge problems. However, the bases of a successful economy are morals and a puritan lifestyle, which so far have characterized rural villages. 70% of the poor and needy live in rural areas in the developing countries and agriculture provides livelihood for 40% of the world’s population. The International Assessment of Agricultural Knowledge, Science and Technology for Development (IAASTD) was established in 2002 by FAO and theWorld Bank to learn more about the role of agricultural science and technology. After the positive decision some comprehensive summaries were made on all the related topics with the participation of 400 scientists. The assessment provided many lessons to learn and at the 2008 closing sessions in Johannesburg, the reports were accepted and it was proved that rural areas have a significant role in providing adequate means of earning a livelihood. The Ministry of Rural Development composed a domestic-level study with the title of the National Rural Strategy. The objectives stated in the study can be seen as the main directions of the Hungarian rural strategy. The land policy aims to support the 50–70 hectare family farms and have the agricultural lands under national authority. The population must be provided with ample and safe food. The priority of local economy, local sale, and local markets is important. The positive exploitation of our natural resources may result in the strengthening of rural areas. The deterioration of rural areas must be stopped. In order to halt these processes swiftly fundamental, patriotic economic and social policy changes, a strong people’s party, a short-run crisis treating and a medium-long-run strategic development and action plan are needed which is based on the respect of work and moral norms, national cooperation, solidarity, and the defense of our mutual interests rather than on speculation (ÁNGYÁN, 2010). The greatest problem of Hungary is low employment.Workplaces may be created in the least expensive and the fastest manner in irrigational agriculture. In order to achieve this, the role of the state must be reconsidered and EU rules on state intervention must be reviewed.